Work-life Balance and Its Impact on the Work Efficiency of Administrative Civil Servants in the Office of the Attorney General, Region 5 - Boonsing, Srisuda; Klomthongjaroen, Kunpatsawee; Sanpatanon, Nateetip; Vannasathid, Prapassorn (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2026)
This research aimed to (1) study the differences in personal factors affecting work performance, (2) study the levels of work–life balance and work performance, and (3) analyze the influence of work–life balance on the work performance of administrative officers under the Office of the Attorney General Region 5. This study employed a quantitative research approach. The population consisted of 484 individuals, and the sample size was determined using Yamane’s formula, resulting in 250 participants selected through purposive sampling. The research instrument was a questionnaire that had been tested for content validity, with the index of item-objective congruence (IOC) meeting acceptable criteria. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics, including independent sample t-test, one-way ANOVA, and multiple regression analysis. The findings revealed that differences in monthly income significantly affected work performance, whereas differences in gender, age, educational level, job position, and marital status did not significantly affect work performance. Furthermore, work–life balance in the dimensions of work, intellectual, family, and financial aspects had a statistically significant positive influence on work performance. In contrast, time-related work–life balance had a statistically significant negative influence on work performance. These findings reflect that the management of work–life balance in each dimension should take into account their differing influences in order to appropriately enhance the work performance of public sector personnel.